Recurrence pattern of rectal cancer after surgical treatment. Analysis of 122 patients in a tertiary care center - Sevá-Pereira,Gustavo (2018)
ABSTRACT Survival in rectal cancer has been related mainly to clinical and pathological staging. Recurrence is by far the most challenging issue when surgical treatment of rectal cancer is concerned. This study aims to establish a recurrence pattern for rectal adenocarcinoma submitted to surgical treatment between March 2003 and July 2016. After exclusion criteria were applied, one hundred twenty two patients were analyzed. Global recurrence was found in 22% of them, while 13.1% have had local recurrence. Disease-free survival was 23.9 months, in average, and medium follow-up was 34.13 months, varying from 6 to 115 months. Recurrence, in literature, is usually between 3 and 35% in 5 years, and shows a 5-years survival rate of only 5%. Around 50% of cases, recurrence is local, confined to pelvis. This data followed literature in most aspects evaluated, although finding a high rate of local recurrence remains a challenge in the seek for better surgical outcomes.